Re/pro/ducing Complexity. - Lodemeyer, Peter; Helen E. Copeland Gallery, Montana State University, Bonzana; Museum Dhondt-Dhaenens, Deurle; Städtische Galerie Villa Zanders, Bergisch Gladbach (Bonn : GlobalArtAffairs, 2012)
Beltjens, Nelleke ; Brouckaert, Hedwig ; Voigt, Jorinde
Helen E. Copeland Gallery, Montana State University, Bozeman, October 7 - 24, 2008 / Museum Dhondt-Dhaenens, Deurle, October 23, 2011 - January 8, 2012 / Städtische Galerie Villa Zanders, Bergisch Gladbach, July 1 - September 16, 2012
kunstcatalogus